Priority Strategy of Intracellular Ca2+ Homeostasis in Skeletal Muscle Fibers during the Multiple Stresses of Hibernation - Jie Zhang; Xiaoyu Li; Fazeela Ismail; Shenhui Xu; Zhe Wang; Xin Peng; Chenxi Yang; Hui Chang; Huiping Wang; Yunfang Gao (Cells, 2019)
Intracellular calcium (Ca2+) homeostasis plays a vital role in the preservation of skeletal muscle. In view of the well-maintained skeletal muscle found in Daurian ground squirrels (Spermophilus dauricus) during hibernation, we hypothesized that hibernators possess unique strategies of intracellular Ca2+ homeostasis. Here, cytoplasmic, sarcoplasmic reticulum (SR), and mitochondrial Ca2+ levels, as well as the potential Ca2+ regulatory mechanisms, were investigated in skeletal muscle fibers of Daurian ground squirrels at different stages of hibernation. The results showed that cytoplasmic Ca2+ levels increased in the skeletal muscle fibers during late torpor (LT) and inter-bout arousal (IBA), and partially recovered when the animals re-entered torpor (early torpor, ET). Furthermore, compared with levels in the summer active or pre-hibernation state, the activity and protein expression levels of six major Ca2+ channels/proteins were up-regulated during hibernation, including the store-operated Ca2+ entry (SOCE), ryanodine receptor 1 (RyR1), leucine zipper-EF-hand containing transmembrane protein 1 (LETM1), SR Ca2+ ATPase 1 (SERCA1), mitochondrial calcium uniporter complex (MCU complex), and calmodulin (CALM). Among these, the increased extracellular Ca2+ influx mediated by SOCE, SR Ca2+ release mediated by RyR1, and mitochondrial Ca2+ extrusion mediated by LETM1 may be triggers for the periodic elevation in cytoplasmic Ca2+ levels observed during hibernation. Furthermore, the increased SR Ca2+ uptake through SERCA1, mitochondrial Ca2+ uptake induced by MCU, and elevated free Ca2+ binding capacity mediated by CALM may be vital strategies in hibernating ground squirrels to attenuate cytoplasmic Ca2+ levels and restore Ca2+ homeostasis during hibernation. Compared with that in LT or IBA, the decreased extracellular Ca2+ influx mediated by SOCE and elevated mitochondrial Ca2+ uptake induced by MCU may be important mechanisms for the partial cytoplasmic Ca2+ recovery in ET. Overall, under extreme conditions, hibernating ground squirrels still possess the ability to maintain intracellular Ca2+ homeostasis.